IMPLEMENTASI KEBIJAKAN DANA DESA DI DESA MENTULIK KECAMATAN KAMPAR KIRI HILIR KABUPATEN KAMPAR TAHUN 2020 - Yonda, Gita Afwah; Marta, Auradian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Mentulik Village is an area in Kampar Kiri Hilir Sub-district, Kampar Regency, Riau Province, which is an expansion sub-district from the parent sub-district, namely Kampar Regency. This village was taken as the object of research with the consideration of being a village that has not been independent among other villages in the Kampar Kiri Hilir District. So this research intends to describe, analyze the implementation of the Village Fund policy in Mentulik Village and analyze the factors that support and hinder the process of implementing the village fund policy in Mentulik Village, Kampar Kiri Hilir District. This research uses George C. Edwards' theory of the four factors that influence policy implementation, namely Communication, Resources, Dispotition, and Bureaucratic Structure. The data used in the research is qualitative. The results of research on the Implementation of Village Fund Policy in Mentulik Village, Kampar Kiri Hilir District, Kampar Regency in 2020 have not gone well. In communication there is a lack of clarity in the information conveyed by superiors to the structures below them, less precise information is conveyed, then there is also a lack of consistency in the information conveyed, times tend to change suddenly. Then the resources, human resources do not understand technology, the community lacks participation, but the facilities and infrastructure are adequate. The disposition, division of tasks and main tasks and functions of the implementers or officials are in accordance with the skills and wishes of each apparatus, but not all of the programs implemented are implemented. Then the provision of technical implementation guidelines (legal basis) for the use of village funds from the central government to Mentulik Village is incorrect. time. In the bureaucratic structure, all officers have carried out their duties in accordance with the implemented SOPs, but this has not been optimal due to existing inhibiting factors. Keywords: Implementation – Village Fund Policy - Mentulik Village